2021
DOI: 10.1155/2021/8492468
|View full text |Cite
|
Sign up to set email alerts
|

Neutrophil-to-Lymphocyte Ratio Facilitates Identification of Obstructive Sleep Apnea in Patients with Type B Aortic Dissection

Abstract: Purpose. To determine whether the neutrophil-to-lymphocyte ratio (NLR) aids in the detection of obstructive sleep apnea (OSA) in patients with type B aortic dissection (TBAD). Methods. 324 patients with TBAD or type B aortic intramural hematoma (TB-AIMH) underwent an overnight sleep study. We divided the eligible 256 studied subjects into three groups: group A (n = 109, TBAD patients with OSA), group B (n = 68, TB-AIMH patients with OSA), and group C (n = 79, TBAD patients without OSA). Baseline characteristic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 39 publications
0
1
0
Order By: Relevance
“…A previous report suggested that NLR could be used as a marker of chronic hypoxic burden in OSA, and therefore as a readily available parameter to evaluate CPAP effectiveness [ 77 ]. Furthermore, NLR was associated with cardiovascular comorbidities in OSA patients [ 79 , 80 ] and was an independent predictor of OSA in three other studies [ 54 , 81 , 82 ]. In a multi-center retrospective study (481 OSA cases and 80 controls) NLR was higher in patients with severe OSA, compared to controls and moderate and mild OSA [ 83 ], and a recent meta-analysis [ 84 ] concluded that neutrophilic inflammation plays a key role in OSA pathogenesis, suggesting that NLR could be viewed as a disease activity biomarker.…”
Section: Discussionmentioning
confidence: 97%
“…A previous report suggested that NLR could be used as a marker of chronic hypoxic burden in OSA, and therefore as a readily available parameter to evaluate CPAP effectiveness [ 77 ]. Furthermore, NLR was associated with cardiovascular comorbidities in OSA patients [ 79 , 80 ] and was an independent predictor of OSA in three other studies [ 54 , 81 , 82 ]. In a multi-center retrospective study (481 OSA cases and 80 controls) NLR was higher in patients with severe OSA, compared to controls and moderate and mild OSA [ 83 ], and a recent meta-analysis [ 84 ] concluded that neutrophilic inflammation plays a key role in OSA pathogenesis, suggesting that NLR could be viewed as a disease activity biomarker.…”
Section: Discussionmentioning
confidence: 97%